Repeated influenza vaccination provides cumulative protection from distinct H3N2 viruses - Kavian, Niloufar (Clin Transl Immunology, 2021)
OBJECTIVES: Current inactivated influenza vaccines provide suboptimal protection against antigenic drift, and repeated annual vaccinations shape antibody specificity but the effect on protection from infection is not well understood. METHODS: We studied the effects of cumulative and staggered vaccinations in mice to determine the effect of influenza vaccination on protection from infection and immune quality. RESULTS: We found that the timing of vaccination and antigenic change impacted the quality of immune responses. When mice received two different H3N2 strains (A/Hong Kong/4801/2014 and A/Singapore/INFIMH‐16‐0019/2016) by staggered timing of vaccination, there were higher H3HA antibody and B‐cell memory responses than four cumulative vaccinations or when two vaccinations were successive. Interestingly, after challenge with a lethal‐drifted H3N2 virus (A/Hong Kong/1/1968), mice with staggered vaccination were unable to produce high titres of antibodies specific to the challenge strain compared to other vaccination regimens because of high levels of vaccine‐specific cross‐reactive antibodies. All vaccination regimens resulted in protection, in terms of viral loads and survival, from lethal challenge, while lung IL‐6 and inflammation were lowest in staggered or cumulative vaccination groups, indicating further advantage. CONCLUSION: Our findings help justify influenza vaccination policies that currently recommend repeat vaccination in infants and annual seasonal vaccination, with no evidence for impaired immunity by repeated seasonal vaccination.